Teaching science and technology in the early years (3-7) - Davies, Dan 1962- (Routledge, 2019)
Teaching Science and Technology in the Early Years (3-7) celebrates young children's amazing capabilities as scientists, designers and technologists. Research-based yet practical and accessible, it demonstrates how scientific designing and making activities are natural to young children, and have the potential for contributing to all aspects of their learning. By identifying the scientific and technological concepts, skills and activities being developed, the book enables the reader to make more focused diagnostic observations of young children and plan for how they can help move them forward in their learning. This third edition has been thoroughly updated and features: fresh insights into young children's learning from neuroscience and 'new-materialist' perspectives; a UK-wide perspective on Early Years curricula and how they support the inclusion of science and technology as an entitlement for young children; new case studies of successful, evidence-based Early Years practice, alongside new examples of practical planning for learning, and advice on documenting children's learning stories; an updated chapter on assessing and documenting children's learning, drawing upon findings from the Teacher Assessment in Primary Science (TAPS) project at Bath Spa University. Based on the latest research and first-hand experience, this practical and accessible book is essential reading for Early Years and Primary students on undergraduate, PGCE and Masters-level courses